A natural series

Calculus Level 2

If the sum of the series n = 2 ln ( 1 1 n 2 ) \displaystyle \sum_{n=2}^{\infty} \ln\left(1 -\frac{1}{n^{2}}\right) can be expressed as ln ( A B ) \ln \left( \dfrac{A}{B}\right) , where A A and B B are positive coprime integers, find A + B A+B .


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Amal Hari
Nov 15, 2019

2 ln ( 1 1 n 2 ) = 2 ln ( n 2 1 n 2 ) \displaystyle \sum_{2}^{\infty} \ln \left( 1-\frac{1}{n^{2}}\right)=\displaystyle \sum_{2}^{\infty} \ln \left( \frac{n^{2} -1}{n^{2}}\right)

2 ln ( n 1 ) ( n + 1 ) n 2 \displaystyle \sum_{2}^{\infty} \ln \frac{\left(n -1\right)\left(n+1\right)}{n^{2}}

ln ( 2 ( n 1 ) ( n + 1 ) n 2 ) \ln\left( \displaystyle\prod^{\infty}_{2} \frac{\left(n -1\right)\left(n+1\right)}{n^{2}}\right)

2 m ( n 1 ) ( n + 1 ) n 2 = ( m 1 ) ! ( m + 1 ) ! 2 ( m ! ) 2 \displaystyle\prod^{m}_{2} \frac{\left(n -1\right)\left(n+1\right)}{n^{2}} =\frac{\left(m -1\right)!\left(m+1\right)!}{2 \left(m!\right)^{2}}

( m 1 ) ! ( m + 1 ) ! 2 ( m ! ) 2 = ( m ) ! ( m ) ! × ( m + 1 ) 2 × m ( m ! × m ! ) \frac{\left(m -1\right)!\left(m+1\right)!}{2 \left(m!\right)^{2}} =\frac{\left(m \right)!\left(m\right)!\times \left(m+1\right)}{2 \times m \left(m! \times m!\right)}

m + 1 2 m \frac{m+1}{2m}

sum of series is natural log of this limiting m to \infty :

lim m ln ( m + 1 2 m ) = ln ( 1 2 m + 1 2 ) = ln ( 1 2 ) \displaystyle\lim_{m\to \infty}\ln\left(\frac{m+1}{2m}\right)=\ln\left(\frac{1}{2m} +\frac{1}{2}\right)=\ln\left(\frac{1}{2}\right)

Great solution! You can also refer to each term t, beginning t=2 as.

ln (t+1) + ln (t-1) - 2ln (t)

As you add up all the terms t, there is a massive cancelling out except for.

ln 1 - ln 2

Which is the same answer!

Max Patrick - 1 year, 6 months ago
Chew-Seong Cheong
Nov 16, 2019

n = 2 ln ( 1 1 n 2 ) = n = 2 ln ( n 2 1 n 2 ) = n = 2 ln ( ( n 1 ) ( n + 1 ) n 2 ) = n = 2 ( ln ( n 1 ) + ln ( n + 1 ) 2 ln n ) = n = 2 ( ln ( n 1 ) ln n ln n + ln ( n + 1 ) ) = n = 2 ( ln ( n 1 ) ln n ) n = 2 ( ln n ln ( n + 1 ) ) = ln 1 ln 2 = ln 2 = ln 1 2 \begin{aligned} \sum_{n=2}^\infty \ln \left(1-\frac 1{n^2} \right) & = \sum_{n=2}^\infty \ln \left(\frac {n^2-1}{n^2} \right) \\ & = \sum_{n=2}^\infty \ln \left(\frac {(n-1)(n+1)}{n^2} \right) \\ & = \sum_{n=2}^\infty \Big(\ln(n-1) + \ln (n+1) - 2\ln n \Big) \\ & = \sum_{n=2}^\infty \Big(\ln(n-1) - \ln n - \ln n + \ln (n+1) \Big) \\ & = \sum_{n=2}^\infty \Big(\ln(n-1) - \ln n \Big) - \sum_{n=2}^\infty \Big(\ln n - \ln (n+1) \Big) \\ & = \ln 1 - \ln 2 = - \ln 2 = \ln \frac 12 \end{aligned}

Therefore, A + B = 1 + 2 = 3 A+B = 1+2=\boxed 3 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...